Dispositivos da infantilidade e da antecipação da alfabetização no currículo do 1º ano do ensino fundamental: conflitos, encontros, acordos e disputas na formação das crianças - Maria Carolina da Silva (2016)
contemporary education. To ensure this, the anticipation of literacy to the age of six - through the extension of Fundamental Education to nine years in length - and the creation of a curriculum that focuses on literacy stand out as two of the main current strategies for early school years. In this thesis, I have used as an object of study a curriculum for the first-year of Fundamental Education at a public school in the city of Belo Horizonte, in order to investigate how it works and what effects early literacy hason the curriculum, teachers and children, as well as what power relations and modes of subjectivity are triggered by it. Through research using elements of postmodern educational ethnography and Foucault-inspired discourse analysis, it was found that the curriculum of the first year of Fundamental Education operates the early literacy device that anticipates knowledge, skills, rules and values commonly taught in the later yearsof schooling, with the goal of producing a literate child at the end of the first year of school. It was also found that the childishness device also concurrently operates in this curriculum. This device has worked with a multitude of speeches, rules, institutions, etc. from the beginning of Modernity to produce a child that is both different from and dependent on adults. This thesis shows that there is a conflict in the curriculum of the first year of Fundamental Education, because the early literacy device needs to eliminate some children marks in order to be effective, while the childishness device works to ensure that children preserve the characteristics they have been endowed with in Modernity. The general thesis developed here is that the early literacy device and the childishness device jostle for space in the curriculum of the first year of Fundamental Education, and in the process, they trigger learning, knowledge, practices, technologies, techniques and procedures that create multiple and conflicting subject positions. Such positions articulate generations, profession, religion, gender, time and also feelings to apply the literacy of children at six years of age, without totally deconstructing the child produced by Modernity.